Variation in reaction to anthracnose within native Stylosanthes capitata populations in Minas Gerais, Brazil - Lenné, Jillian M. (Scientific Societies, 1988)
Native populations of Stylosanthes capitata, a promising perennial pasture legume in tropical America, were evaluated for their reaction to a virulent widespread race of Colletotrichum gloeosporioides. Considerable variation in anthracnose reaction among progenies from individual plants, among plants from the same site, and between populations from the same and different sites in Minas Gerais, Brazil, was found. The greatest diversity for anthracnose reaction among progeny was shown by population Diamantina B (Shannon Index of Diversity h = 0.39), whereas the least was found in Mendanha B (h = 0.17). Although the majority of progenies were susceptible, highly resistant progenies were found in all populations. Results suggest that diversity in anthracnose resistance within native S. capitata populations contributes to their persistence in the presence of virulent C. gloeosporioides and emphasize the importance of maintaining diversity in improved S. capitata pastures in agroecosystems where C. gloeosporioides is endemic.